Audit fee setting : a new perspective - Lee, Yan Yeow (2014)
General studies (including Simunic [1980], Palmrose [1986], Francis & Simon [1987], Francis [1984] and Francis & Stokes [1986]) have primarily focused on factors like firm size variable, complexity and risk. To date, most of these models have theoretically argued and empirically supported an objective perspective on the determinant factors. The model which we propose to adopt allows for control of time lag factors beyond those which have so far been considered in any literature. Specifically, the argument is that prior year's audit fee should have a presence in establishing the current year's fee. Our results support this argument.